The effect of a shelf placement intervention on sales of healthier and less healthy breakfast cereals in supermarkets: A co-designed pilot study. (December 2020) - Young, Leanne; Rosin, Magda; Jiang, Yannan; Grey, Jacqui; Vandevijvere, Stefanie; Waterlander, Wilma; Ni Mhurchu, Cliona
Abstract: Supermarkets are the principal source of grocery food in many high-income countries. Choice architecture strategies show promise to improve the healthiness of food choices. A retailer-academic collaboration was formed to co-design and pilot selected commercially sustainable strategies to increase sales of healthier foods relative to less healthy foods in supermarkets. Two co-design workshops, involving supermarket corporate staff and public health nutrition academics, identified potential interventions. One intervention, more prominent shelf placement of healthier products within one category (breakfast cereals), was selected for testing. A pilot study (baseline, intervention and follow-up, 12-weeks each) was undertaken in six supermarkets (three intervention and three control) in Auckland, New Zealand. Products were ranked by nutrient levels and profile, and after accounting for the supermarkets' space management principles, healthier products were placed at adult eye level. The primary outcome was change in sales of healthier products relative to total category sales. Secondary outcomes were nutrient profile of category sales, in-store product promotions, customer perceptions, and retailer feedback. There was no difference in proportional sales of more prominently positioned healthier products between intervention (56%) and control (56%) stores during the intervention. There were no differences in the nutrient profile of category sales. A higher proportion of less healthy breakfast cereals were displayed in intervention versus control stores (57% vs 43%). Most customers surveyed supported shelf placement as a strategy (265, 88%) but noted brand preferences and price were more salient determinants of purchases. Retailers were similarly supportive but balancing profit, health/nutrition and customer satisfaction was challenging. Shelf placement alone was not an effective strategy to increase purchases of healthier breakfast cereals. This study showed co-design of a healthy eating intervention with a commercial retailer is feasible, but concurrent retail environment factors likely limited the public health impact of the intervention. Highlights: Co-designing healthy eating interventions with supermarket retailers is feasible. Altered shelf placement alone did not improve the healthiness of food purchases. Customers noted brand preferences and price as key determinants of purchases. In-store promotions present opportunities to improve healthiness of food purchases. Product promotional strategies should align with healthy eating interventions.